Kinetics Study & Evaluation od Adsorbent Capacity for Fe2O3 - Pebriani
Syngas is a mixture of gas mostly CO and H2 which is obtained through steam reforming natural gas, gasification of coal or biomass. In natural gas, besides shortchain hydrocarbons, there are also impurities commonly found. One of them is the variety of sulfur gas substances. Sulfur gas compounds are toxic compounds that appear widely in input gases for industries such as gasification of coal, natural gas, and liquified petroleum gases (LPG). The presence of these compounds, even in just a few ppm, can lead to corrosion of equipment and piping, poison the catalyst, and lead to economic losses on a large scale. The process of adsorption of H2S and other sulfur compounds from various gases uses iron adsorbents is one of the oldest processes that has been found.